An investigation of self-regulated learning of young adults in a business vocational education and training program - Liveris, Christine (Curtin University, 2012)
National reform in vocational education and training (VET) and the raising of the school leaving age legislation in Western Australia have resulted in an increasing proportion of young adults in VET programs. VET teaching and learning practices are learner-centred, work-centred and attribute-focused. A shift from a teacher-centred approach to a more learner-centred approach can be a major transition for some younger learners. The challenge for practitioners is to help these young adults develop generic, transferable employability skills and attributes, in order to facilitate self-directed lifelong learning.Educational psychologists and policy makers view academic self-regulation as the key to successful learning in school and further education; however, agree that most learners struggle to attain this in their methods of study. The term ‘academic self-regulation’ is synonymous with self-directed learning. The primary research question for this study was: What are the self-regulatory characteristics of 18- to 24-year-olds completing a business administration assessment? Specifically: 1 What cognitive strategies did they use to comprehend and perform the task? 2 What metacognitive strategies did they use to control and regulate their cognition? 3 How did they regulate their behaviour?Within the framework of a social cognitive view of learning, this study adopted a phenomenological approach. A purposive sample group of eight students aged from 18 to 24, participated in the study. Participants were full-time Certificate IV Business Administration students enrolled at a TAFE college in Perth, Western Australia. Their four teachers also participated. This study was intended to produce inferences that may suggest ways we can better understand academic self-regulation.Semi-structured interviews with the participants were undertaken after the submission of a written assessment task and the teachers were interviewed at the end of the semester. Raw data were coded using broad categories from Pintrich’s (2004) theoretical framework. Data were then reduced to clusters of statements and placed into categories. Case by case results provide a snapshot of each case and cross-case results have been reported under six major themes. Quality control was achieved through a combination of data from participant interviews, teacher interviews and the researcher’s interpretations; the latter have been linked to previous research and reviewed through peer debriefing.Findings suggest that the self-regulation characteristics of these young learners are dependent on a range of factors, including: purpose of engagement; differences in developmental stage, culture, commitments, and learning environment; and the task. This thesis identifies areas for further research; specifically, the relationship between personality and styles of self-regulation, practitioner education programs that support early identification and intervention for students with learning difficulties and the impact of internet distractions on time and effort.